The effect of flax seed extract on the blood glucose level and liver bio markers in diabetic rats - Mustafa Al-Ahmad, Basma Ezzat; Dally, Imad Matloub; Abired, Ahmed N.; Saad, Azzubaidi Marwan; Emad, Mohamad Nafie (2019)
Prescribed medications used to treat diabetes do not adequately inhibit the development of its associated complications, furthermore, they may cause different side effects. Hence, there is a demand for alternative therapies to manage diabetes and its associated complications. This study aimed to evaluate the hepatoprotective effects of flaxseed extract in streptozotocin(STZ)-induced diabetic rats. Diabetes mellitus was induced in Sprague-Dawley rats using a single injection of streptozotocin (60 mg/kg, intraperitoneally). The rats were divided into five groups of 8 animals each: Group NC, normal control rats; Group NF, normal rats treated with flaxseed extract (400 mg/kg); Group DC, diabetic control rats; Group DG, diabetic rats treated with glibenclamide (0.6 mg/kg); Group DF, diabetic rats treated with flaxseed extract (400 mg/kg); for 4 weeks. Body weight, liver relative weight, blood glucose level and liver enzymes were determined in all experimental rats. Results showed a significantly increased relative liver weight, blood glucose, AST, ALT, GGT, ALP, and LDH levels, and decreased body weight, total protein, albumin, and globulin levels in DC group comparing to NC group (p<0.05). The disturbance of these parameters was ameliorated in DF and DG groups, however, the ameliorative effect was significant in DG group only (p<0.05). These pathological changes were ameliorated in the flaxseed extract and glibenclamide treated rats. In conclusion, our data showed that flaxseed extract represents a potential alternative treatment to control diabetes mellitus and its related hepatopathy